Effectiveness of Transformational Leadership to Improve Work Environment and Nurses' Job Satisfaction: A Systematic Review - Ayidh, M. Alrashidi Nasser (International Journal of Research in Interdisciplinary Studies, 2025)
In recent years, leadership style and job satisfaction have become important issues in the healthcare system. Various nursing leadership styles have a direct or indirect impact on the nursing profession, and quality of patient care. The discussion regarding the influence of leadership style on nurses' job satisfaction focus on how various leadership style affect the work environment and the quality of care delivered by nursing professionals. Transformational leadership has become one of the leadership styles believed to have a positive effect on nurses job satisfaction, work environment, and performance. This review primarily focused on evaluating the influence of transformational leadership style on the work environment and nurses' job satisfaction. Objective: The review aimed at assessing the effectiveness of transformational leadership style to improve work environment and job satisfaction among nurses. Methods: A systematic literature review approach was used. Comprehensive literature searches were conducted in PubMed, MEDLINE, CINAHL, Web of Science, and Research4Life. The main search terms used in the databases were “Transformational leadership and nurses, and job satisfaction." All English articles published between 2019 and 2024 reporting the effectiveness of transformational leadership on work environment and nurses' job satisfaction were eligible for inclusion. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines was used to select cross-sectional studies. Results: Five articles were included in the review. These studies were conducted in healthcare settings, with a total of 1285 nurses and they reported the positive influence of transformational leadership on nurses’ job satisfaction, work environment and the quality of care provided by nurses. Conclusion: The transformational leadership style significantly enhances job satisfaction among nurses. Consequently, it is advisable for healthcare organizations to adopt a transformational leadership style to improve the work environment and nurses' job satisfaction.